Descriptive norms and entrepreneurial intentions: the mediating role of anticipated inaction regret - Bae, Tae Jun; Lee, Chong Kyoon; Lee, Younggeun; McKelvie, Alexander; Lee, Woo Jin (Frontiers in Psychology, 2024)
Previous research has mainly focused on the cognitive-based theory of planned behavior (TPB) model to predict entrepreneurial intentions. However, given the close relationship between cognition and emotion, researchers may need to pay more attention to how emotional reactions help predict entrepreneurial intentions. To fill this gap, we apply both cognitive (i.e., descriptive norms) and emotional (i.e., anticipated inaction regret) aspects to understand predictors of entrepreneurial intentions. Specifically, we employ the affect-as-information perspective as a complementary theoretical lens to TPB to test whether the role of descriptive norms on entrepreneurial intentions is affected by anticipated inaction regret as a form of emotional reaction to descriptive social norms. We conducted two survey-based studies with diverse samples (i.e., online Mturk panels of adults in the US and undergraduate students in Korea). This study demonstrates (1) a positive and significant relationship between descriptive norms and entrepreneurial intentions and (2) a mediating role of anticipated inaction regret between descriptive norms and entrepreneurial intentions. Our results contribute to the entrepreneurial intentions literature by exploring the mechanism between cognition and emotion, and highlighting an indirect emotional link (i.e., anticipated inaction regret) in understanding entrepreneurial intentions.